SIFAT FISIKO-KIMIA MINYAK KERUING YANG DIHASILKAN DARI METODE PENYULINGAN UAP (The physico-chemical properties of Keruing oils obtained by steam distillation technique) - Bambang Wiyono (Pusat Penelitian dan Pengembangan Hasil Hutan, 1996)
Keruing oils can be obtained through separating the oil from keruing gum by distillation technique, or distilling keruing wood. In accordance with the lattest method, the objective of this research is to study the physico-chemical properties of keruing oils which were obtained by steam distillation of a mixture of several keruing wood species. This wood was randomly taken three times from the wastes of wood processing industry in East Kalimantan. Each wood wastes taken was steam distilled and the yielded oils were analysed their physico-chemical properties. The difference between means value of the properties of the oils was tested by using LSD according td SAS procedure.Results revealed that wood wastes gave a highly significant effect on refractive index, optical rotation, acid and ester number of keruing oils. It also gave a significant effect on saponification number. Further analysis showed that the keruing oil with clear colour compared to both keruing oil with clear yellow and pale yellow colour was a significant difference in acid and ester number. Moreover, the keruing oil with pale yellow colour had ll significant difference in saponification number compared the others. Among these oils, the refractive index and optical rotation properties were a significant difference one to the others. Based these results, if the keruing wood wastes will be used as raw materials for keruing oil production, it is better that the keruing wood containing much oil or gum should be separated from the others before further processing.Keywords: Keruing oil, Dipterocarpus spp, Steam distillation, oil properties